Culture, differentiation, and transduction of mouse E12.5 pancreatic spheres: an in vitro model for the secondary transition of pancreas development. Issue 1 (4th March 2021) - Huijbregts, Lukas; Aiello, Virginie; Soggia, Andrea; Ravassard, Philippe; Rachdi, Latif; Scharfmann, Raphaël; Albagli, Olivier
ABSTRACT: During the secondary transition of rodent pancreatic development, mainly between E12.5 and E15.5 in mice, exocrine and endocrine populations differentiate from pancreatic progenitors. Here we describe an experimental system for its study in vitro . First, we show that spheres derived from dissociated E12.5 mouse pancreases differentiate within 7 days into most pancreatic exocrine and endocrine cell types, including beta cells. The proportion and spatial repartition of the different endocrine populations mirror those observed during normal development. Thus, dissociation and culture do not impair the developmental events affecting pancreatic progenitors during the secondary transition. Moreover, dissociated cells from mouse E12.5 pancreas were transduced with ecotropic MLV-based retroviral vectors or, though less efficiently, with a mixture of ALV(A)-based retroviral vectors and gesicles containing the TVA (Tumor Virus A) receptor. As an additional improvement, we also created a transgenic mouse line expressing TVA under the control of the 4.5 kB pdx1 promoter ( pdx1 -TVA). We demonstrate that pancreatic progenitors from dissociated pdx1 -TVA pancreas can be specifically transduced by ALV(A)-based retroviral vectors. Using this model, we expressed an activated mutant of the YAP transcriptional co-activator in pancreatic progenitors. These experiments indicate that deregulated YAP activity reduces endocrine and exocrine differentiation in the resulting spheres, confirming and extending previously published data. Thus, our experimental model recapitulates in vitro the crucial developmental decisions arising at the secondary transition and provides a convenient tool to study their genetic control.